Exploring the Implementation of Challenge-Based Learning (CBL): A Pathway to Student Motivation and Self-Regulated Learning - Abdelkader Makhlouf; Hanane Rabahi (International Journal of Educational Development, 2025)
This research analyses the implementation of Challenge-Based Learning (CBL) at Algerian universities and its potential for encouraging undergraduate learners to academically acquire learning, enhancing self-regulated learning strategies, and enhancing interdisciplinarity collaboration. This research adopted the mixed-method approach and used a quantitative tool (the Motivated Strategies for Learning Questionnaire (MSLQ)) and obtained qualitative data through reflective journals, interviews, and classroom observation. Outcomes show that CBL greatly affects enhancing students' motivation and supporting self-directed actions such as goal-setting, time management, and metacognitive processing. Interdisciplinary cooperation was also determined to be supportive for student engagement and problem-solving capacity. Students and instructors predominantly reported positive opinions regarding CBL, highlighting the relevancy, authenticity, and cooperation aspects of CBL. These findings validate the four study hypotheses and endorse the pedagogical shift towards active, student-centered learning in Algerian universities. The research concludes with strategic suggestions to institutionalize CBL, reassess assessment practices, and encourage professional development in support of the faculty utilizing this new pedagogy.